Peningkatan Pemahaman Konsep Siswa pada Materi Pewarisan Sifat Melalui LKS Berbantuan Media di SMPN 2 Selat Tahun Ajaran 2022/2023 - Agathe Agathe; Suandi Sidauruk; Vera Amelia (Departement of Mathematics Education, 2023)
This study aims to improve students' conceptual understanding of inheritance by using worksheets. This type of research is descriptive. It was carried out in the second semester of Academic Year 2022/2023. The subjects were the students of Grade IX at SMPN 2 Selat in Academic Year 2022/2023. The research was conducted with five (5) learning stages they were Pre-LKS, LKS, Post-LKS, Discussion, and Post-Discussion. Research data were obtained by using tests given to students at the Pre-LKS, Post-LKS and Post-Discussion stages. The results of the study show the changes in students' understanding of concepts as follows: : (1) Indicator 1 explains the role of genetic material in determining traits, the average number of students who answered correctly was 46.38% at the pre-worksheet stage, 81.16% at the post-worksheet stage, increased to 82.61% in the post-discussion stage. (2) Indicator 2 determines the results of monohybrid crosses through diagrams according to the laws of inheritance, the average number of students answering correctly was 33.04% in the pre-worksheet stage, 37.39% in the post-worksheet stage, increasing to 60.00% in the post-worksheet stage discussion. (3) Indicator 3 makes a cross chart according to the data that has been presented, the average number of students who answered correctly was 45.65% in the pre-LKS stage, 56.52% in the post-LKS stage, increasing to 70.72% in the post-LKS stage discussion. The data of this study indicate that the use of media assisted worksheets can improve students' conceptual understanding of inheritance.